Infrared laser moxibustion for cancer-related fatigue in breast cancer survivors: a randomized controlled trial - Huijuan Mao; Ming Jin; Lulu Xie; Ni Mao; Xubo Shen; Junchao Chen; Xuefen Chen; Jun J. Mao; Xueyong Shen (Breast Cancer Research, 2024)
Abstract Background Cancer-related fatigue (CRF) is a pervasive, persistent, and distressing symptom experienced by cancer patients, for which few treatments are available. We investigated the efficacy and safety of infrared laser moxibustion (ILM) for improving fatigue in breast cancer survivors. Methods A three-arm, randomized, sham-controlled clinical trial (6-week intervention plus 12-week observational follow-up) was conducted at a tertiary hospital in Shanghai, China. The female breast cancer survivors with moderate to severe fatigue were randomized 2:2:1 to ILM (n = 56) sham ILM (n = 56), and Waitlist control (WLC)(n = 28) groups. Patients in the ILM and sham ILM (SILM) groups received real or sham ILM treatment, 2 sessions per week for 6 weeks, for a total of 12 sessions. The primary outcome was change in the Brief Fatigue Inventory (BFI) score from baseline to week 6 with follow-up until week 18 assessed in the intention-to-treat population. Results Between June 2018 and July 2021, 273 patients were assessed for eligibility, and 140 patients were finally enrolled and included in the intention-to-treat analysis. Compared with WLC, ILM reduced the average BFI score by 0.9 points (95% CI, 0.3 to 1.6, P = .007) from baseline to week 6, with a difference between the groups of 1.1 points (95% CI, 0.4 to 1.8, P = .002) at week 18. Compared with SILM, ILM treatment resulted in a non-significant reduction in the BFI score (0.4; 95% CI, -0.2 to 0.9, P = .206) from baseline to week 6, while the between-group difference was significant at week 18 (0.7; 95% CI, 0.2 to 1.3, P = .014). No serious adverse events were reported. Conclusion While ILM was found to be safe and to significantly reduce fatigue compared with WLC, its promising efficacy against the sham control needs to be verified in future adequately powered trials. Trial registration Clinicaltrials.gov: NCT04144309. Registered 12 June 2018.